Pengaruh Kinerja Keuangan dan GCG Terhadap Nilai Perusahaan dengan CSR Sebagai Variabel Moderasi - Widiyani, Nur; Maslichah, Maslichah; Nandiroh, Umi (e_Jurnal Ilmiah Riset Akuntansi, 2026)
This study aims to examine the effect of financial performance and Good Corporate Governance (GCG) on firm value, with Corporate Social Responsibility (CSR) as a moderating variable. The research is motivated by inconsistent empirical findings regarding the determinants of firm value, particularly in the insurance sector, which is characterized by high risk, strict regulation, and strong dependence on public trust. Financial performance is proxied by the Debt to Equity Ratio (DER), GCG is measured using the ASEAN Corporate Governance Scorecard (ACGS), firm value is represented by Tobin’s Q, and CSR disclosure is assessed based on the Global Reporting Initiative (GRI) 2021 standards. This study employs secondary data obtained from annual and sustainability reports of 13 insurance companies listed on the Indonesia Stock Exchange during the 2022–2024 period, resulting in 39 observations. The data are analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that financial performance has a positive and significant effect on firm value, while GCG does not significantly affect firm value. In addition, CSR does not have a direct effect on firm value. However, CSR is proven to strengthen the relationship between financial performance and firm value, but fails to moderate the relationship between GCG and firm value. These findings support Signalling Theory, suggesting that financial performance serves as the primary signal for investors and is reinforced by adequate CSR disclosure. Meanwhile, CSR activities tend to be perceived as long-term stakeholder-oriented practices rather than immediate value-enhancing signals, and GCG practices that emphasize formal compliance have not been regarded as value-relevant signals by the market. This study implies that insurance companies should optimize capital structure management and integrate CSR as a strategic tool to enhance sustainable firm value.Keywords: Firm value; financial performance; good corporate governance; corporate social responsibility; insurance companies